Evaluation of Antioxidant, Free Radical Scavenging, and Antimicrobial Activity of Quercus incana Roxb. - Sarwar, Rizwana; Farooq, Umar; Khan, Ajmal; Naz, Sadia; Khan, Sara; Khan, Afsar; Rauf, Abdur; Bahadar, Haji; Uddin, Reaz (Frontiers in Pharmacology, 2015)
Considering the indigenous utilization of Quercus incana Roxb., the present study deals with the investigation of antioxidant, free radical scavenging activity, total phenolic content and antimicrobial activity of Quercus incana Roxb. In vitro antioxidant activity of the plant fractions were determined by DPPH and NO scavenging method. Total phenolic contents were determined by gallic acid equivalent (GAE) and antimicrobial activities were determined by agar well diffusion method. It was observed that Quercus incana Roxb. showed significant antibacterial activity against Gram-positive and Gram-negative bacteria. n-Butanol fraction showed maximum activity against Micrococcus leuteus with 19 mm zone of inhibition. n-Butanol fraction of Quercus incana Roxb. showed immense antifungal activity against Aspergillus niger (32 mm ± 0.55) and Aspergillus flavus (28 mm ± 0.45). Similarly n-butanol fraction showed relatively good antioxidant activity with IC50 value of 55.4 ± 0.21μg/mL. The NO scavenging activity of ethyl acetate fraction (IC50 = 23.21 ± 0.31 μg/mL) was fairly good compared to other fractions. The current study of Quercus incana Roxb. suggests the presences of synergetic action of some biological active compounds that may be present in the leaves of medicinal plant. Further studies are needed to better characterize the important active constituents responsible for the antimicrobial, antioxidant and free radical scavenging activity.